Features of interaction between law enforcement agencies during the investigation of criminal offenses according to international standards: Características de la interacción entre los órganos de aplicación de la ley durante la investigación de delitos penales según las normas internacionales - Chaplynskyi, Kostiantyn; Yefimov , Mykola; Pletenets , Viktor; Harashchuk, Diana; Demchenko, Irina (Political Questions, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*113.39px); top: calc(var(–scale-factor)*276.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14325);" role="presentation">The purpose of the research was to highlight the interaction <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*287.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15435);" role="presentation">between law enforcement agencies during the investigation of <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*298.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05935);" role="presentation">crimes in accordance with international standards. It also highlights <span dir="ltr" style="left: calc(var(–scale-factor)*99.21px); top: calc(var(–scale-factor)*309.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0991);" role="presentation">the main areas of cooperation between law enforcement agencies <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*320.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09093);" role="presentation">in different States during the investigation of criminal offenses. Taking into <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*331.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09993);" role="presentation">account the great public danger of criminal offenses, it is worth noting that <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*342.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12652);" role="presentation">they have long since acquired a transnational character and it is therefore <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*353.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1116);" role="presentation">interesting to pay special attention to the issue of cooperation between the <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*364.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08583);" role="presentation">National Police of Ukraine and various international police organizations in <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*375.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.1009);" role="presentation">the investigation of this category of criminal offenses. The methodological <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*386.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.18043);" role="presentation">basis of the research is presented as comparative-legal and systematic <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09562);" role="presentation">analysis, <span dir="ltr" style="left: calc(var(–scale-factor)*100.88px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08982);" role="presentation">formal-legal <span dir="ltr" style="left: calc(var(–scale-factor)*160.91px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13046);" role="presentation">method, <span dir="ltr" style="left: calc(var(–scale-factor)*203.81px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.13467);" role="presentation">method <span dir="ltr" style="left: calc(var(–scale-factor)*244.02px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03721);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*258.81px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.14824);" role="presentation">interpretation, <span dir="ltr" style="left: calc(var(–scale-factor)*329.70px); top: calc(var(–scale-factor)*397.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.12887);" role="presentation">hermeneutic <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*408.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.15716);" role="presentation">method, as well as methods of analysis and synthesis. Among the main <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*419.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09007);" role="presentation">conclusions, it draws attention to the necessity of the issue of strengthening <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*430.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.08621);" role="presentation">cooperation between the operational units of the National Police of Ukraine <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*441.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.17875);" role="presentation">engaged in the fight against criminal offenses and international police <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*452.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09516);" role="presentation">bodies engaged in operational and investigative activities, as a condition of <span dir="ltr" style="left: calc(var(–scale-factor)*56.69px); top: calc(var(–scale-factor)*463.03px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.09873);" role="presentation">possibility to combat crime in all its manifestations.